2012
DOI: 10.1007/s10735-012-9456-5
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of connective tissue in patients with pelvic organ prolapse

Abstract: The uterosacral ligaments are an important part of the pelvic support system. The objective of this study was to compare the expression of collagen type I and collagen type III in the uterosacral ligament biopsies from women with and without pelvic organ prolapse (POP). The uterosacral ligament biopsies were obtained from women with POP (n = 29) and non-POP subjects (n = 35). Immunohistochemistry for collagen type I and collagen type III was performed on formalin-fixed and paraffin-embedded sections. The two g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 26 publications
2
25
0
3
Order By: Relevance
“…Vulic et al (24) and Chen et al (25) reported that the amounts of collagen I and III were significantly decreased in USL with POP. However, there are different opinions, as Yucel et al (26) clarified that the expression of collagen III was upregulated in women with POP. Gabriel et al (8) concluded that there was no significant difference in the expression of collagen I between women with POP and or women with non-POP, but an increased ratio of collagen I/III may be a salient feature of POP.…”
Section: Discussionmentioning
confidence: 99%
“…Vulic et al (24) and Chen et al (25) reported that the amounts of collagen I and III were significantly decreased in USL with POP. However, there are different opinions, as Yucel et al (26) clarified that the expression of collagen III was upregulated in women with POP. Gabriel et al (8) concluded that there was no significant difference in the expression of collagen I between women with POP and or women with non-POP, but an increased ratio of collagen I/III may be a salient feature of POP.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] Several studies have compared the amount of total and individual subtypes of collagen in the supporting ligaments and vaginal tissue of women with POP to a control group (see Table 1). 19,[23][24][25][26][27][28][29][30][31][32][33][34][35][36] Figure 1 Current anatomical considerations for prolapse. Level 1: The upper 1/3 of the vagina is suspended to the pelvic wall by the uterosacral and cardinal ligaments, condensations of endopelvic fascia.…”
Section: Collagen Compositionmentioning
confidence: 99%
“…Несмотря на противоречивые данные, в це-лом у пациенток с ПГ отмечают снижение содержания общего коллагена с более высо-ким содержанием коллагена III типа -не-зрелого и менее прочного [14]. Детерминация нарушения содержания при ПГ коллагена III типа наличием полиморфизма гена COL3A1 определяет интерес к ряду генетичес-ких исследований [13].…”
Section: Im Sechenov First Moscow State Medical University Moscowunclassified
“…По-добные данные приводят и другие авторы, оценивавшие сопоставимые по возрасту, ин-дексу массы тела и длительности постмено-паузы выборки [14].…”
Section: Im Sechenov First Moscow State Medical University Moscowunclassified